Analisis Pengaruh Bentuk Wing Tip Terhadap Performa Aerodinamika Sayap Pesawat Terbang Radio Controlled Menggunakan Ansys 2022R1 - Firmanto, Bondhan (Akademi Angkatan Udara, 2022)
As is the case with actual aircraft production, model aircraft are made in several stages. One of the most important stages in the manufacture of an aircraft is designing the wings and testing their aerodynamic performance. The wing is the main part of the aircraft because it is the part of the aircraft that produces the most lift. Likewise, in the manufacture of model aircraft, the aerodynamic performance of the wings needs to be designed and analyzed so that the aircraft can fly stably and show optimal aerodynamic performance. In this study, three variations of the shape of the NACA2812 wing tip will be analyzed to determine the optimal aerodynamic performance. Aerodynamic analysis was performed numerically using the ANSYS 2022R1 software package. The compute domain was created using the ANSYS DesignModeler software. 3D wing model with NACA2812 airfoil. Mesh was created using ANSYS Meshing software. Simulation using ANSYS Fluent software. The turbulence model used is k-omega SST in transient, incompressible, subsonic, and sea level conditions. The simulation is run at a speed of 8.33 m/s and an angle of attack of 0°. The analysis focuses on the aerodynamic performance of the CL, CD, CL/CD, and visualization of fluid pressure around the wing. The results of the analysis show that the infinite wing tip design produces a lift coefficient value of 0.249437106, a drag coefficient value of 0.032376252, and a lift to drag ratio of 7.704323091 (the lowest value of lift to drag ratio). The design of the cut off wing tip produces a lift coefficient value of 0.292337624, a drag coefficient value of 0.025722932, and a lift to drag ratio value of 11.36486404. The aft swept wing tip shape design produces a lift coefficient value of 0.322231093, a drag coefficient value of 0.027981121, and a lift to drag ratio value of 11.51601789 (the highest lift to drag ratio value). Therefore, the design of radio controlled aircraft will use a wing design with an aft swept wing tip shape.